2022
DOI: 10.1007/s11255-022-03276-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of percutaneous renal biopsy performed using 18G needle versus 16G needle: a single-center retrospective study

Abstract: Background At present, both 16G and 18G needles are used for percutaneous renal biopsy in China. This study aimed to compare the efficacy and safety of biopsy performed with the 18G needle vs. the 16G needle. Methods The data of patients who underwent percutaneous renal biopsy at our hospital between January 2015 and December 2019 were retrospectively analyzed. The number of glomeruli obtained by puncture and postoperative complications were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…Theoretically, the larger lumen of the 16-gauge needle should allow for more tissue to be harvested during each pass, thus increasing the potential for obtaining more glomeruli. However, contrary to our study findings, [ 24 ] found no significant difference in the number of glomeruli obtained between 16- and 18-gauge needles. This discrepancy might be attributed to sample size or technique variations across the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the larger lumen of the 16-gauge needle should allow for more tissue to be harvested during each pass, thus increasing the potential for obtaining more glomeruli. However, contrary to our study findings, [ 24 ] found no significant difference in the number of glomeruli obtained between 16- and 18-gauge needles. This discrepancy might be attributed to sample size or technique variations across the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of 16-gauge needle was associated with an increased mean number of obtained glomeruli, which is consistent with previous literature included in the current review [ 8 , 13 , 16 , 18–20 , 22 , 24 ]. Theoretically, the larger lumen of the 16-gauge needle should allow for more tissue to be harvested during each pass, thus increasing the potential for obtaining more glomeruli.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, invasive renal biopsy has a considerable risk of serious complications (e.g., gross hematuria, perirenal hematoma, arteriovenous fistula, etc.) ( 9 ). Hence, a non-invasive method of monitoring renal function and assessing RF would be a valuable tool to diagnose CKD and guide antifibrotic therapy.…”
Section: Introductionmentioning
confidence: 99%